Dietary phytochemicals with anti-oxidant and pro-oxidant activities: A double-edged sword in relation to adjuvant chemotherapy and radiotherapy?. (28th June 2019) - Fernando, Wasundara; Rupasinghe, H.P. Vasantha; Hoskin, David W.
Abstract: Many advances have been made in the development and introduction of new anti-cancer drugs to the clinic. However, limited attention has been paid to improving the efficacy of currently available treatments through complementary phytochemical interventions that affect cellular reactive oxygen species (ROS) levels, which are important for the etiology of certain cancers and the effectiveness of radiotherapy and some chemotherapy. In this regard, the maintenance of redox homeostasis may be influenced by the intake of anti-oxidant and pro-oxidant compounds from dietary sources. Interestingly, certain dietary phytochemicals exhibit both anti-oxidant and pro-oxidant activities, depending on their concentration and cellular microenvironment. There is evidence that concurrent administration of some dietary phytochemicals enhances the efficacy of certain cancer treatments by increasing intracellular ROS accumulation. Paradoxically, consumption of the same dietary phytochemicals under conditions that result in the scavenging of ROS might also negatively affect the outcome of ROS-dependent cancer treatments. This review discusses the potential impact of consuming dietary phytochemicals with anti-oxidant and/or pro-oxidant activities on the effectiveness of concurrent chemotherapy and/or radiotherapy in cancer patients. Highlights: Under some conditions, certain phytochemicals exhibit both anti- and pro-oxidant activities. Pro-oxidant phytochemicals may enhance the efficacy of ROS-governed cancer treatments. Anti-oxidant phytochemicals may reduce the efficacy of ROS-dependent cancer treatments.